PEMBUATAN GAME ADVENTURE “DETECTIVE ADVENTURE” MENGGUNAKAN UNITY VIRTUAL REALITY - Yohanes Yohanes; Jeanny Pragantha; Darius Andana Haris (Jurnal Ilmu Komputer dan Sistem Informasi, 2020)
“Detective Adventure” is a Virtual Reality game for Android using cardboard. Where the detective must seek clues to reveal a serial killer by investigating crime scene. This game use three-dimensional graphics and virtual reality headset. The game uses a remote Virtual reality to pick up item and move. This game created by Unity game engine with C# as programming language and photoshop to make object, and to edit image. Testing was done with the blackbox testing, alpha testing by lecturer, and beta testing by surveying 30 respondens. Respondens show that the “Detective Adventure” is an interesting game to play.